Spatial configuration by rules: an experimental parametric shape rules by shape grammar method - Alva F. P. Sondakh; Aswin Indraprastha (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
This study investigated the method of Shape Grammar to develop a computational technique to generate spatial configuration at the early stage of the design process. In synthesizing the spatial configuration and its variants, the user (i.e., architect) can use this tool as a heuristic way to select and choose a spatial configuration of geometric shapes to represent functional requirements and their relationships. We studied the example of Adolf Loos's residential works as our basis for the parametric shape rules and the tool developed in the form of a modular cluster component in the Visual Programming Language Grasshopper in a Rhinoceros 3D modeling software. This cluster component, termed